SISTEM INFORMASI KEUANGAN DAERAH DAN GOOD GOVERNANCE - Rudi Kurniawan, . (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2010)
ABSTRACT Government Regulatory No.56/2005 urges the local government to adopt local financial information system (SIKD). Various information supplied by the local government is essentially a process of local financial accounting system  being set and presented in accordance with the government accounting standard. The aim of SIKD is  therefore to assist the head of local government to manage and assume responsibility the local finance in order to enhance transparancy and accountability in implementing good governance. If SIKD were being performed properly, the good governance of local government would be realized. Unfortunately, reality is still far from expected due to some concomittant problems.   Kata Kunci : Sistem Informasi Keuangan Daerah, Sistem Akuntansi Keuangan Daerah, Good Governance, Akuntabilitas.